2022
DOI: 10.2196/30527
|View full text |Cite
|
Sign up to set email alerts
|

Embedding and Integrating a Digital Patient Management Platform Into Everyday Primary Care Routines: Qualitative Case Study

Abstract: Background Traditional primary care is characterized by patient consultations via phone and physical visits. However, the current development in Swedish primary care is to blend digital solutions with traditional solutions. This paper addresses this development by examining the normalization of embedding and integrating a digital health care platform into everyday care routines in a primary care clinic. The digital health care platform enables both synchronous (video calls) and asynchronous (chat) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The findings from our study highlight areas where the platform impact on quality of services, increasing the understanding of how it could be of best use. Recognising the importance of the implementation process, which has been addressed in several other studies of e-health innovations including similar platforms, and the time and effort it takes to put in place new routines in already existing everyday work practices [ 25 ], our study also brings to the forefront areas where quality gains could potentially be made and where further development of similar platforms should direct its focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from our study highlight areas where the platform impact on quality of services, increasing the understanding of how it could be of best use. Recognising the importance of the implementation process, which has been addressed in several other studies of e-health innovations including similar platforms, and the time and effort it takes to put in place new routines in already existing everyday work practices [ 25 ], our study also brings to the forefront areas where quality gains could potentially be made and where further development of similar platforms should direct its focus.…”
Section: Discussionmentioning
confidence: 99%
“…Frennert et al. [ 25 ] describe the process to implement and sustain a similar platform and its practices into everyday work processes and found that new routines and practices were accepted if staff perceived them as beneficial. The findings suggest that similar platforms might do well to target specific patient groups where benefits are identified rather than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a research project on the impacts on the working environment and primary healthcare professionals when transforming traditional primary healthcare practices into digitally mediated practices. As part of the project, we have explored the implementation process of a digital patient management platform [38] in regard to normalisation process theory [39]. In this article, we primarily aim to examine healthcare professionals' experiences of working with patient management through a digital patient management platform.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 29 31 Although eHealth solutions have been studied for years, there remains a gap in understanding of how the materiality of eHealth solutions affects care and care work. 18 , 32 34 Leornadi 35 defines materiality as ‘the arrangement of an artefact's physical and/or digital materials into particular forms that endure across differences in place and time and are important to users’. He argues that the material aspects of technology become materialised in a context and evolve in that context, that is, they are not fixed.…”
Section: Introductionmentioning
confidence: 99%
“…An eHealth solution can belong to one of these domains or contain elements from several domains. 3 Research on eHealth has focussed on changed roles for healthcare professionals, [4][5][6] the importance of alignment with care processes, [7][8][9] impact of staff turnover, 10 increased workload 11 and/or decreased workload, [12][13][14] changes in workflow [15][16][17][18] and changes in professional values. 5,7,19 Consequently, previous research shows that eHealth solutions influence the way healthcare professionals conduct their work and provide care.…”
Section: Introductionmentioning
confidence: 99%